State-Mediated Fiqh and the Regulation of Muslim Interfaith Marriage in Southeast Asia - Kamaluddin, Imam; Lahuri, Setiawan bin; Hidayat, Iman Nur; Nasution, Saipul; Kanggas, Fazari Zul Hasmi; Mahmud, Hafini bin (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
Interfaith marriage involving Muslims remains a contentious issue in contemporary Islamic family law, particularly where classical jurisprudence intersects with state authority. This article examines the interpretation, codification, and regulation of classical Islamic doctrines within the legal frameworks of Indonesia, Malaysia, and Brunei Darussalam. Utilizing a comparative legal approach, the study analyzes statutory regulations, judicial precedents, and administrative policies concerning marriage with Ahl al-Kitāb. The findings reveal that, while all three nations draw on the Shāfiʿī school, their regulatory outcomes diverge due to variations in institutional design and the state's role in mediating Islamic law. Indonesia exhibits a dynamic model of legal pluralism, where administrative and judicial interpretations have historically created limited spaces for interfaith registration despite normative restrictions. Malaysia maintains a structured dual legal system characterized by jurisdictional separation and mandatory conversion requirements. Brunei Darussalam employs a highly centralized model of Islamic legal authority, resulting in an absolute prohibition without alternative recognition mechanisms. Ultimately, this study demonstrates that interfaith marriage regulation is shaped by the institutional transformation of Fiqh into enforceable state law, contributing to broader debates on legal pluralism and the "mujtahid state".